Risk factors for difficult‐to‐treat hepatitis C virus genotype 4r in Rwanda and implications for elimination in sub‐Saharan Africa. Issue 4 (2nd February 2021) - Shumbusho, Fabienne; Liu, Anne F.; Kateera, Fredrick; Kabahizi, Jules; Nsanzaimana, Sabin; Serumondo, Janvier; Damascene Makuza, Jean; Grant, Philip M.; Musabeyezu, Emmanuel; Muvunyi, Claude; Gupta, Neil
Abstract: In sub‐Saharan Africa, there exist distinct HCV genotype (GT) subtypes harbouring resistance‐associated substitutions to commonly used non‐structural protein 5A (NS5A) inhibitor–based direct‐acting antiviral (DAA) regimens. In particular, GT4r subtype has demonstrated high rates of treatment failure. In the absence of routine viral sequencing in sub‐Saharan Africa, it is important to identify sociodemographic, epidemiologic, and clinical characteristics that may be associated with GT4r infection. Methods: A secondary analysis was performed on data from 300 adults with HCV GT4 enrolled in a prospective trial assessing the safety and efficacy of sofosbuvir‐ledipasvir in Rwanda in 2017. The association between characteristics at enrolment and GT subtype was assessed by chi‐square analysis and logistic regression. In multivariate analysis, there were a higher proportion of participants with GT4r subtype with age <40 years (OR: 3.6, 95% CI: 1.3–10.5, p  = 0.02), previous hospitalization (OR: 2.5, 95% CI: 1.3–5.0, p  = 0.006), previous surgery (OR: 2.2, 95% CI: 1.1–4.2, p  = 0.03), cirrhosis (OR: 3.2, 95% CI: 1.3–7.5, p  = 0.008) and baseline HCV RNA >1 million IU/ml (OR: 3.4, 95% CI: 1.6–6.9, p  = 0.001). Rwandan adults with GT4r are more likely to be younger, have a history of hospital admissions and surgeries and have more active or advanced liver disease compared to those with other GT4 subtypes. In the absence of advanced diagnostics to assess GT subtype, patients with these characteristics may warrant closer monitoring for treatment failure or alternative DAA regimens. More treatment experience with diverse DAA regimens is urgently needed for GT subtypes particular to this region.